2009
DOI: 10.3109/03630260903351882
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Globin Induction in β-thalassemia

Abstract: Thalassemia patients with persistently high levels of fetal globin typically have less severe anemia, have milder clinical syndromes, and are often transfusion independent. Therefore, the search for molecules exhibiting the property of inducing gamma-globin gene expression and fetal hemoglobin (HbF) production is of great interest. Different pharmacological agents have been studied, namely erythropoietin, short chain fatty acids and cytotoxic agents, azacytidine, and hydroxycarbamide. Hemoglobin F inducers fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Red wine, particularly the skin of black grapes, contains resveratrol which mimics the HbF-inducing activity of HU. Its role in increasing the γ-globin mRNA in human erythroid precursors has been confirmed [84].…”
Section: Natural Inducersmentioning
confidence: 94%
See 2 more Smart Citations
“…Red wine, particularly the skin of black grapes, contains resveratrol which mimics the HbF-inducing activity of HU. Its role in increasing the γ-globin mRNA in human erythroid precursors has been confirmed [84].…”
Section: Natural Inducersmentioning
confidence: 94%
“…Epigenetic modifiers of HbF can be grouped in several classes, with different mechanisms of action. Different epigenetic modifiers of γ-globin gene are namely: erythropoietin, short chain fatty acids and cytotoxic agents, azacytidine, and hydroxycarbamide [84] (Table 1). [85].…”
Section: • Epigenetic Modifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of patients show significant microcytosis and some borderline anemia, the increase of Hb A 2 that mostly distinguishes b-thalassemia minor from other conditions like iron-deficiency anemia is absent in a small proportion of b-thalassemia carriers (silent carriers) [2,11]. Main clinical features in these patients are hypertrophy of erythroid marrow with medullary and extramedullary hematopoiesis and its complications.…”
Section: Clinical Picture Of Inherited Hemoglobin Disordersmentioning
confidence: 99%
“…It was observed that activation of p38 MAPK (mitogen activated protein kinase) pathway and deactivation of ERK (extracellular signal regulated kinase) pathway led to an increase in higher expression of gamma globin gene and an increase in the level of HbF in treated cells. Increase in gamma globin gene expression and level of foetal Haemoglobin by activation of p38 MAPK pathway and deactivation of ERK pathway, has been observed in cells treated with different naturally occurring pharmacological and chemical compounds, such as cucurbitacin D, hydroxy urea, butyrate, an ethanol extract of Fructus trichosanthis, resveratrol [18,24,44,45]. On the basis of available literature, it may be concluded piceatannol treatment may increase the expression of gamma globin gene and result in increase in foetal Haemoglobin production in beta thalassaemia patients, because activation of p38 MAPK pathway and deactivation of ERK pathway have been confirmed in piceatannol treated cells [46].…”
Section: Assumption Based On Previous Studiesmentioning
confidence: 99%